2020
DOI: 10.1002/ijgo.13107
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and perinatal outcomes and factors associated with twin pregnancies among preterm births: Evidence from the Brazilian Multicenter Study on Preterm Birth (EMIP)

Abstract: Objective: To compare maternal and perinatal outcomes between twin and single preterm births (PTB) and associated factors. Methods:A cross-sectional multicenter study was conducted in Brazil with 4046 PTBs from April 2011 to July 2012. Causes of PTB, use of tocolytics, corticosteroids, and antibiotics in twin and single pregnancies, and factors possibly associated with twinning were evaluated using χ 2 tests. Maternal and perinatal outcomes were assessed with prevalence ratios (PR). Results:The main cause of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 34 publications
6
3
0
Order By: Relevance
“…The incidence of preterm birth in twin pregnancies found in this research was comparable to prior studies (13,15,17,18). Drawing from the work of Santana et al, our study echoes the nding that the primary culprit behind preterm births in twin pregnancies is the spontaneous onset of preterm labor, accounting for 74.7% of the preterm twin births recorded here (19). Other studies, like those by Oger et al and Feng et al, corroborate our observations that neonates from monochorionic twin pregnancies face heightened morbidities.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The incidence of preterm birth in twin pregnancies found in this research was comparable to prior studies (13,15,17,18). Drawing from the work of Santana et al, our study echoes the nding that the primary culprit behind preterm births in twin pregnancies is the spontaneous onset of preterm labor, accounting for 74.7% of the preterm twin births recorded here (19). Other studies, like those by Oger et al and Feng et al, corroborate our observations that neonates from monochorionic twin pregnancies face heightened morbidities.…”
Section: Discussionsupporting
confidence: 89%
“…The past decade has seen a rise in the prevalence of twin deliveries. The recorded rate of 1.99% per 100 live births in this study is higher than gures reported in previous Thai studies conducted between 2004-2009 (13, 14) but align well with studies from the decade of the current study (15,(18)(19)(20)(21). The incidence of preterm birth in twin pregnancies found in this research was comparable to prior studies (13,15,17,18).…”
Section: Discussionsupporting
confidence: 87%
“…The twin birth rate in China has dramatically risen over the last decade, from 16.4‰ in 2007 to 21.7‰ in 2014, owing to the widespread use of assisted reproductive technology and increased maternal age 1 . Twin pregnancies are associated with increased perinatal morbidity and mortality, given that they are at increased risk for spontaneous preterm birth (sPTB), about half of twin pregnancies are delivered preterm, 2,3 and it is unclear whether any intervention reduces this risk 4–8 …”
Section: Introductionmentioning
confidence: 99%
“…are delivered preterm, 2,3 and it is unclear whether any intervention reduces this risk. [4][5][6][7][8] Cervical cerclage represents one of the best-known surgical interventions to prevent sPTB in obstetrics.…”
mentioning
confidence: 99%
“…Due to inherent biological factors, a twin pregnancy is associated with various adverse perinatal outcomes and maternal obstetrics complications [ 11 ]. Preterm birth, low birth weight, twin to twin transfusion syndrome, perinatal deaths, and admission to neonatal intensive care unit (NICU) are among many adverse perinatal outcomes associated with twin pregnancy [ 12 , 13 ]. For example, the rate of perinatal mortality among twin pregnancies could be up to six times higher compared to singleton pregnancies [ 11 ].…”
Section: Introductionmentioning
confidence: 99%